Mampukah Kurs Berdampak Terhadap Indeks Saham Syariah Indonesia? Kajian Empiris Selama Pandemi Tahun 2020-2021 - Ach. Fauzi Lutfi; Ridan Muhtadi (IQTISADIE: Journal of Islamic Banking and Shariah Economy, 2022)
This study aims to see how much influence the exchange rate has on the Indonesian Sharia Stock Index in 2020-2021. The method used in this study is a quantitative method with a simple regression analysis technique. The data collection technique uses secondary data obtained from the websites of Bank Indonesia and the Financial Services Authority. The results of this study indicate that the exchange rate variable has a significant influence on the Indonesian Sharia Stock Index variable which is seen from the F-statistic probability value below the alpha value of 0.0011 < 0.05. The Exchange Rate variable has a negative relationship with the Indonesian Sharia Stock Index with a coefficient value of -394.3737. This means that the higher the exchange rate, the lower the value of the Indonesian Sharia Stock Index.